O programa imagético da Paixão de Cristo das Ordens Terceiras do Carmo: contraponto entre história, iconografia, materiais e técnicas de esculturas devocionais dos séculos XVII-XIX no Brasil - Lia Sipaúba Proença de Moraes (2019)
Make the actual images and with its humanized features was the main feature of the works reproduced by the universe of modern european empires with the purpose of spreading the catholic religion overseas. One of the mendicant orders, the carmelites came to Brazil in the second half of the 16th century, supported by the portuguese crown, for an installation of convents and churches throughout the empire. The third order of Carmo perpetuated in many ways the devotion to the figure of human Jesus Christ reflected in ornamentation of the temples. Be a part of a third order meant being in communion among brothers and condition of sociability for the pursuit of a built life. This study aims to analyze the imagery program of sculptures of the Passion of Christ of third orders of Carmo from the portuguese Empire in the following theoretical-practical aspects: historical dimension, iconographic, uses/functions, techniques and materials. In this way, we conducted a counterpoint between the sodalícios carmelites brazilians in Salvador and Cachoeira (BA), in São Cristóvão (SE), in Rio de Janeiro (RJ), São Paulo, Mogi das Cruzes, Itu and Santos (SP) and, finally, in São João Del Rei, Mariana, Ouro Preto, Diamantina, Serro and Sabará (MG). This comparison is based by the interface of material and immaterial contingencies to devotion to the Suffering Christ and in celebration of the triumphal procession. The methodology used was the bibliographic survey in the areas of History, Art and Iconography, apart from documentary research in archives, photographic record and in situ investigation at the localities bounded. It is concluded that the images of the Passion of Christ were assimilated, acclimated and accommodated under the circumstances and the needs of the everyday life of the faithful of these third orders. This Thesis demonstrates that this type of sculptural collection is designed as a source of understanding the world of men, since they are living documents and experiences of past and present life.